Kegiatan Rutin Senam Lansia Di Desa Pekik Nyaring Bengkulu Tengah - Yugita, Ira; Elpina, Elpina; Andriani, Zulfa; Rustandi, Handi; Nurjana, Nimas Ayu (Universitas Dehasen Bengkulu, 2024)
The elderly are a group of individuals who are more than 60 years old and are the final stage of development followed by several gradual changes or commonly called aging. Elderly gymnastics is a series of regular, directed and patterned tone mobility that is followed by the elderly which is carried out with the intention of increasing the functional ability of the body to achieve this goal. In addition to elderly gymnastics activities, deep breathing exercises can also be done to maintain the health of the elderly (Rosmaharani & Noviana, 2022). One of the impacts of dementia that occurs in the elderly is cognitive impairment in the form of decreased memory or senility. In addition, according to (Kurniasari, 2022) the impact of dementia is affecting the communication skills, cognitive, emotional and behavioral abilities of the elderly. Improving the quality of life in the elderly can be done through elderly gymnastics. The purpose of this Community Service is to provide gymnastics training to the elderly in Hamlet III, Pekik Nyaring Village. This community service has been carried out from May 29, 2024 to June 9, 2024. The evaluation of activities is based on pre and post questionnaire data. The results of Community Service show that the elderly have enough knowledge as many as 21 people (70%). After the implementation of the elderly gymnastics, the knowledge became good for 27 people (90%). Conclusion The implementation of gymnastics can improve the quality of life of the elderly.